Прокрастинація як аспект поведінки педагога та шляхи її подолання - Єременко, Лариса В'ячеславівна; Еременко, Лариса Вячеславовна; Yeremenko, Larysa; Ісакова, Олена Іванівна; Исакова, Елена Ивановна; Isakova, Olena; Тараненко, Галина Григорівна; Тараненко, Галина Григорьевна; Taranenko, Halyna; Шлєіна, Людмила Іванівна; Шлеина, Людмила Ивановна; Shlieina, Liudmyla (ТДАТУ, 2020)
UK: У статті представлено огляд досліджень феномена прокрастинації, підходів до класифікації прокрастинації. Також проаналізовано причини виникнення прокрастинації, її структурна організація, запропоновано алгоритм подолання прокрастинації для педагогів. EN: The review of researches of the prokrastination’s phenomenon, approaches to classification of a prokrastination is presented in this article. In the article the reasons of emergence of a prokrastination are also analyzed, its structural organization, the algorithm of its overcoming is presented.
Procrastination as a behavior’s aspect of teacher and ways to overcome it
Keywords: феномен прокрастинації; прокрастинатор; перфекціонізм; копінг-стратегія; самооцінка; phenomenon of prokrastination; procrastinator; perfectionism; koping-strategy; training; self-assessment